Lettuce yield response to application of rhizobacteria and nitrogen to the growth substrate - Morais Menezes, Ana Paula; Kusdra, Jorge Ferreira; Moreno, Andreia de Lima (Comunicata Scientiae, 2024)
Rhizobacteria of agronomic interest can promote plant growth, increase productivity, and reduce the demand for nitrogen (N) fertilizers by improving the N use efficiency in crops. The objective of this study was to assess the effects of rhizobacteria and nitrogen on the yield of lettuce plants (cultivar Vera). The experiment was carried out in a greenhouse, using a completely randomized design in a 2×2×2×2 factorial arrangement, with five repetitions. The factors consisted of single and combined applications of liquid inoculants (1 mL) based on Azospirillum brasilense, Bacillus subtilis, and Bradyrhizobium japonicum, as well as nitrogen (75 kg ha-1) in the growth substrate. The variables assessed were total and commercial shoot fresh and dry weights, root dry weight, total dry weight, and numbers of total and commercial leaves, and shoot nitrogen content. Lettuce yield components improved with nitrogen fertilizer application. The single application of rhizobacteria did not increase lettuce yield, as the plants had decreases in root weight in response to Bradyrhizobium japonicum and decreases in total and commercial shoot dry weights, root dry weight, and total dry weight when Bacillus subtilis was used. However, the combined application of Azospirillum brasilense, Bacillus subtilis, and nitrogen increased the lettuce number of commercial leaves and shoot nitrogen content when one or another microbial specie was associated with nitrogen fertilizer.